COMPARISON OF FAILURE RATE OF TEMPORARY ANCHORAGE DEVICES PLACED WITH PLATELET RICH PLASMA AND PLACEBO OVER SIX MONTHS: A SPLIT MOUTH RANDOMIZED CLINICAL TRIAL - Ahmad, Nofil; Durrani, Owais Khalid; Faiza Ijaz; Zuhaa Mushtaq; Iram Abbas (Journal of Ayub Medical College Abbottabad, 2024)
Background: The aim of this in vitro research was to compare and evaluate the stability of TADs coated with PRP over 6 months. TAD stability is essential for the long-term success of orthodontic treatment. PRP has become a valuable adjunct to promote healing in many procedures of oral surgery. The use of PRP in combination with bone grafts in dental treatments yields positive results in terms of improving the handling properties of the grafts and enhancing the quantity and quality of the newly formed bone. Methods: This study was conducted at Islamic International Dental College, Orthodontic Department for 6 months from April 2018 to February 2019. It was a triple-blinded study using split-mouth randomized clinical trial. Comparison of Failure of Temporary Anchorage Devices inserted with Platelet Rich Plasma and Platelet Poor Plasma (placebo) was done on 25 patients with TADs placed on the right and left sides (total of 50 TADs). Patients who had visited for comprehensive orthodontic treatment were screened according to inclusion and exclusion criteria to be included in the study. The consent form was designed in which the procedure and the reason for the study were explained to every patient selected. Each patient was given the consent form which was signed by the patient. Injection of a few drops of PRP into the pilot hole by an 18 gauge needle syringe and similarly PPP (Placebo) onto the opposing site was done. The operator was blinded during the procedure. Patients were advised to report if there was any failure of TAD.TADs were assessed on every orthodontic visit (monthly) for 6 months. Results: The total number of patients was 25, each with TAD on both the right and left sides. In a total of 50 TADs, 5 (10%) failed, 4 (8% of the total) of the left side and 1 (2% of the total) of the right side Out of these 25, 14 (56%) were males and 11 (44%) were females. In 25 patients only 1 (4%) patient showed both left and right side failure while 4 (16%) patients showed only left side failure. In terms of PPP (placebo) and PRP, the rate of failure were 3 (12%) of PPP and 2 (8%) for PRP. The mean days of failure were 46.00±3.22 and 6.50±9.192 for PPP and PRP respectively. Conclusion: From this study, it was noticed that there was no significant difference in the stability of TADs injected with PRP or PPP (placebo). Other factors such as gender, and patient or operator handedness were also not significant.